The visa application process at the South African High Commission in Swaziland in the context of national security - Hlongwane, Zanele Gladys (My University, 2014)
Every country has the sovereign right to decide who may or may not enter its territory. Possession of a visa does not guarantee automatic admission to the Republic of South Africa (RSA). It only authorises the holder to proceed to the Republic to report to an immigration officer at a port of entry for the purpose of being examined as to his / her ability or otherwise, to comply with the entry requirements. The purpose of a visa on the one hand is to ensure proper screening of applicants so that undesirable persons are not admitted to the Republic and on the other hand to facilitate the entry of approved applicants at South African ports of entry. Visa provides immigration officers with the necessary information to ensure that applicants are admitted for the correct purpose and period into the RSA. Visa and immigration policy together determine who can come into South Africa for admission. This paper explores visa process at the South African High Commission in Swaziland in the context of national security. The survey for visa applicants and staff members at the mission was conducted in order to determine the challenges that are faced during visa processing. The paper concludes by putting forward suggested recommendations that can assist in improving the efficiency and effectiveness of the visa process at the mission in the context of national security.
Thesis (M.M. (Security))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: Immigration policy; National security; Visa applications; South Africa